Electron Microscopy: Liquid‐Flowing Graphene Chip‐Based High‐Resolution Electron Microscopy (Adv. Mater. 2/2021). Issue 2 (12th January 2021) - Koo, Kunmo; Park, Jungjae; Ji, Sanghyeon; Toleukhanova, Saltanat; Yuk, Jong Min
Abstract : In article number 2005468, Jong Min Yuk and co‐workers develop a novel operando imaging platform, "liquid‐flowing graphene‐chip transmission electron microscopy". Featured with graphene viewing windows and anti‐bulging supports, this novel method provides controllable liquid thickness and structural integrity under a high degree of pressure gradient and fast liquid circulation. These "liquid‐flowing graphene chips" provide atomic‐resolution imaging and molecular‐level information for inorganic and biological samples, and can be applicable to in situ heating and biasing experiments.